2020
DOI: 10.1177/0194599820941499
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus–Associated Anogenital Pathology in Females With HPV‐Positive Oropharyngeal Squamous Cell Carcinoma

Abstract: We sought to determine the incidence and location of human papillomavirus (HPV)–associated anogenital disease in women with HPV-positive oropharyngeal squamous cell carcinoma (OPSCC) via a retrospective cohort study with prospective contact to update history at Mayo Clinic in Rochester, Minnesota. Females undergoing treatment for nonmetastatic HPV-positive OPSCC from 2011 to 2019 were identified. Clinical history and outcomes were abstracted from medical records. Patients without documented anogenital history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Among women with a primary diagnosis of oral cancer, the number of secondary cervical cancers was lowest among medical record-based studies ( 122 , 123 ), followed by provincial registries ( 121 , 127 ), and highest among national studies ( 112 , 113 , 117 , 120 , 126 ). National studies reported that the incidence of a secondary cervical cancer ranged from 4.5-192.5 per 10,000 women ( 112 , 113 , 117 , 120 , 126 ) ( Table 3C ).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Among women with a primary diagnosis of oral cancer, the number of secondary cervical cancers was lowest among medical record-based studies ( 122 , 123 ), followed by provincial registries ( 121 , 127 ), and highest among national studies ( 112 , 113 , 117 , 120 , 126 ). National studies reported that the incidence of a secondary cervical cancer ranged from 4.5-192.5 per 10,000 women ( 112 , 113 , 117 , 120 , 126 ) ( Table 3C ).…”
Section: Resultsmentioning
confidence: 96%
“…Although we specifically included studies focused on HPV-related oral cancers, the sites of oral cancers varied across studies (e.g., some studies included oropharynx, oral cavity and pharynx, some only included oropharyngeal, and some vaguely defined HPV-related head and neck sites). Five studies examined the risk of a secondary cervical cancer after a primary diagnosis of oral cancer ( 113 , 120 123 ). Half of the studies (n=11/22, 50%) examined the risk of a secondary oral cancer diagnosis after a primary diagnosis of a cervical cancer (n=6) ( 106 108 , 111 , 115 , 116 ) or a cervical intraepithelial neoplasia (CIN) (n=5) ( 109 , 110 , 118 , 124 , 125 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is considered to be one of the leading causes of death in patients that have been cured from their primary OPSCC [19]. The HPV oncogenic properties at other cancer sites and in particular the anogenital organs are well demonstrated [35,36]. In this regard, in a recent study investigating sequential acquisition of HPV infection between genital and oral anatomic sites in males, Dickey et al showed that the Hazard ratio of a sequential genital to oral HPV infection was 2.3 (95% CI: 1.7-3.1) and 3.5 (95% CI: 1.9-6.4) for oral to genital infection [35].…”
Section: Hpv-positive and Hpv-negative Opscc Are Two Distinct Diseasesmentioning
confidence: 99%